Experimental investigation of thermo-physical properties, convective heat transfer and pressure drop of functionalized graphene nanoplatelets aqueous nanofluid in a square heated pipe - Yarmand, H.; Gharehkhani, S.; Shirazi, S.F.S.; Amiri, A.; Alehashem, M.S.; Dahari, M.; Kazi, S.N. (Elsevier, 2016)
In the present study, a facile method is used for preparation of functionalized graphene nanoplatelets (f-GNP) nanofluids. The effective thermal conductivity, density, viscosity, specific heat capacity, overall heat transfer coefficient and friction factor for fully developed turbulent flow of f-GNP/water nanofluids flowing through a square pipe at a constant heat flux were studied. f-GNP uniform nanocomposite was produced from a simple acid treatment reaction procedure. The surface characterization was performed by various techniques such as XRD, FESEM, FTIR and Raman. The f-GNP nanofluids were prepared by dispersing the functionalized nanoparticles in base fluid (water) without the assistance of a surfactant. As made nanofluids were stable for a long time and no sedimentation was observed. The experimental data for f-GNP nanofluids have shown significant enhancement in thermal conductivity and overall heat transfer coefficient in comparison to the corresponding water data. The percentage of enhancement is a function of weight concentration of nanoparticles and temperature. Highest improvement of overall heat transfer coefficient is 19.68% with 9.22% raise in friction factor for the weight concentration of 0.1% at a Reynolds number of 17,500 compared to those data from the base fluid.